Environmental sustainability of the biogas pathway in Italy through the methodology of the Global Bioenergy Partnership. (10th October 2021) - Pirelli, Tiziana; Chiumenti, Alessandro; Morese, Maria Michela; Bonati, Guido; Fabiani, Stefano; Pulighe, Giuseppe
Abstract: Biogas production and use can represent a win-win strategy providing multiple opportunities to mitigate the emission of greenhouse gases responsible for climate change, while offering a range of important social, environmental and economic benefits. Nevertheless, as for other bioenergy pathways, biogas sustainability needs to be carefully assessed and continuously monitored in light of the specific geographic and temporal context in which it performs. This paper aims to provide a comprehensive review on the sustainability assessment of domestic production and use of biogas in Italy, with a focus on the environmental dimension of the sustainability. Furthermore, it elaborates the results of the review to perform an ex-novo sustainability assessment of biogas pathway at national level, through the methodology developed by the Global Bioenergy Partnership. The biogas value chain in Italy can play a positive role to foster the transition towards an ecological and circular economy. This paper highlights both weaknesses and strengths of the biogas value chain in Italy and points out existing differences, in relation to the sustainability of the value chain, between various geographical areas of the country. The outcomes of this study could inform, both at national and international scale, the drawing of tailor-made policies and measures to reduce biogas-related potential risks of environmental impacts, as well as to support the replication and scaling up of successful management practices. Furthermore, they could serve as a baseline for the future monitoring of the sector. Ultimately, the paper reports the key difficulties encountered in the implementation of the GBEP methodology and the solutions adopted to overcome them. Graphical abstract: Image 1 Highlights: Three-quarters (75.4%) of the Italian biogas production takes place in the Po river valley, one-third comes from Lombardy. Maize silage and livestock manure are the most common feedstocks in Italian biogas plants. Roughly 80 k tons of nitrogen contained in livestock manure were treated by biogas plant in Italy in 2016. The main source of GHG emissions along the biogas pathway in Italy lies in the cultivation of dedicated bioenergy crops. Water shortage hampers the development of the biogas sector in southern Italy, restricting the cultivation of energy crops.